Linking Planning with Budgeting: Examining Linkages between General Plans and Capital Improvement Plans. (March 2019) - Mathur, Shishir
Scholars and practitioners in the United States have paid significant attention to the need for consistency in urban planning documents. However, consistency between general plans (GPs) and capital improvement plans (CIPs) has received little attention. Aiming to fill this research gap, this article first reviews the academic and professional literature to identify the strategies that local governments use to ensure strong consistency between GPs and CIPs. Then, it reviews the GPs and CIPs of four cities and presents a framework for evaluating whether, how, and how well local governments are implementing strategies that enhance GP–CIP consistency.